Tra economia della religione ed economia religiosa. Spigolature italiane di storia e teoria economica (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Una rivoluzione contraddittoria - 3. Chiesa e denaro: la questione del prestito a interesse - 4. La svolta della Rerum Novarum: associazionismo e cooperazione - 5. Cattolicesimo e corporativismo - 6. Gli anni ’30 e l’eclissi dell’economia liberale - 7. Il dopoguerra italiano: un miracolo a metà - 8. Gli effetti negativi dei cattolici in politica, Giovanni Paolo II e il dialogo con il mercato.Between the Economics of Religion and Religious Economics. Tangent Questions Regarding Italian History and Economic Theory.ABSTRACT: The paper discusses the most important points of the relationship between social Christian thought and economic facts and how they developed in Italy, with particular reference to the application of competitive market principles. Starting with the second half of the 1800s, it is possible to argue that both the social doctrine and market theories had scarse impact on each other and more importantly, that they did not interact in a way which would have been useful. The author covers the main and most significant contributions that economists, sociologists, philosophers and politicians tried to bring to this missing debate between economic science and religious principles. In view of the creation of a society which responds to mankind’s real needs, we feel the lack of such a debate even though today we are witnessing a certain awakening.